Ratio between left and right ventricular end-diastolic volumes and outcomes in patients with heart failure and preserved ejection fraction. (3rd October 2022) - Aimo, A; Teis, A; Kasa, G; Junca, G; Lupon, J; Domingo, M; Ferrer, E; Vallejo, N; Cediel, G; Codina, P; Lopez-Ayerbe, J; Martini, N; et al.
Abstract: Background: Reference left and right ventricular (LV/RV) volumes normalized to age and gender have been published. However, the relative dilation of the LV compared to the RV in patients with heart failure (HF) symptoms and its prognostic association have not been evaluated. Purpose: The present study investigated the relative dilation of the LV compared to the RV among patients with HF and preserved LV ejection fraction (HFpEF). We explored the association between LV/RV ratio (defined as the ratio between LV end-diastolic volume index [LVEDVi] and RV end-diastolic volume index [RVEDVi]) and outcomes. Methods: Clinical and imaging data from consecutive ambulatory patients diagnosed with HFpEF between April 2011 and November 2021, and undergoing a cardiac magnetic resonance examination were retrieved. The endpoints were 1) all-cause death or first HF hospitalization, and 2) cardiovascular death or first HF hospitalization, 3) repeated HF hospitalizations. Results: A total of 159 patients (median age 58 years [interquartile range 49–69], 64% men) were included. Median LVEF was 60% (54–70%), and the LV/RV ratio was 1.21 (1.07–1.40). Over a 3.5-year follow-up (1.5–5.0), all-cause death or first HF hospitalization occurred in 23 patients (15%) and cardiovascular death or first HF hospitalization in 22 (14%). Spline curve analysis showed a bimodal relationship between LV/RV and both outcomes, with a steep increase in risk <1.0 and ≥1.4 (Figure 1). Accordingly, patients with either LV/RV <1.0 or ≥1.4 had a much shorter survival free from both endpoints than patients with LV/RV 1.0–1.3 (Figure 2). An LV/RV <1 was associated with a higher risk of all-cause death or first HF hospitalization (hazard ratio [HR] 5.95, 95% confidence interval [CI] 1.67–21.28; p=0.006) and a higher risk of cardiovascular death or first HF hospitalization (HR 5.68, 95% CI 1.58–20.35; p=0.008). Furthermore, an LV/RV ≥1.4 was associated with a higher risk of all-cause death or first HF hospitalization (HR 4.10, 95% CI 1.58–10.61; p=0.004) and a higher risk of cardiovascular death or first HF hospitalization (HR 3.71, 95% CI 1.41–9.79; p=0.008). Nine patients (6%) had more than 1 HF hospitalization. The crude incidence of HF hospitalizations was much higher in patients with an LV/RV <1.0 (16.6 per 100 patient/years) or ≥1.4 (10.29 per 100 patient/years) than in those with LV/RV 1–1.3 (1.88 per 100 patient/years). Multivariable binomial negative regression showed significant association between LV/RV and recurrent HF hospitalizations after adjustment by age, gender and New York Heart Association class: LV/RV <1.0 vs. 1.0–1.3, incidence rate ratio 9.0 per 100 patient/years (4.1–19.6), p<0.001; LV/RV ≥1.4 vs. 1.0–1.3, incidence rate ratio 5.3 per 100 patient/years (1.5–8.4), p=0.009. Conclusions: Among patients with HFpEF, an RVEDVi larger than the LVEDVi, or an LVEDVi ≥40% larger than the RVEDVi were significantly associated with worse outcomes. Funding Acknowledgement: Type of funding sources: None.